Perbedaan Kecenderungan Adiksi Gadget Siswa Sekolah Dasar Ditinjau dari Jenis Kelamin - Ni Putu Rizky Arnani; Fatiya Halum Husna (Psycho Idea, 2021)
This study examines whether there are differences in the tendency of gadget addiction in terms of gender in elementary school students. The research subjects were 60 elementary school students grade 4,5 and 6 who were selected using purposive sampling. . The data analysis technique used is independent sample t-test. Statistical analysis result with independent samples t-test showed that there was significant difference in the tendency of gadget addiction in terms of the sex of male and female students (t = 3,229, p = 0.002, p <0.05). This shows that the research hypothesis is accepted which means that there are differences in the tendency of gadget addiction in terms of gender. Men have an average tendency of gadget addiction tendencies that is higher at 51.53 compared to female students at 47.62.